Pengaruh Kualitas Pelayanan, Kewajaran Harga, dan Fasilitas Terhadap Kepuasan Pelanggan Melalui Minat Pelanggan Gym Pada Saat Pendemik Covid-19 (Studi Kasus Andalas Gym Jakarta) - Fauzen (Journal of Economics and Business Aseanomics, 2024)
This study aims to analyze and describe the factors that influence customer satisfaction. The research method, namely, Structural Equation Modeling (SEM), using the SmartPLS application. The results of the analysis show that the coefficient value of the influence of the service quality variable on customer satisfaction is 0.311, the standard error value is 0.129, the t-statistic value is 2.420 > 1.96 (> ttable) and the p-value is 0.016 (< 0.05), so reject H0. It can be concluded that service quality has a positive and significant effect on customer satisfaction at a significance level of 5%.